Transformasi Ekonomi Kreatif dan Kewirausahaan di Kelurahan Rungkut Kidul Untuk Mendukung Pengembangan UMKM - Rifqi Agata Geovani Pratama; Aufa Izzudin Baihaqi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Indonesia as a unitary republic has a lot of wealth in its various varieties, both natural and cultural, including food and handicrafts. Indonesian food and beverage products are well managed by various industries in the territory of Indonesia, and involve the active role of MSME actors. MSMEs, which are built by individuals or business entities, play a role in producing and meeting the needs of the surrounding community. Although they face various obstacles in product development and sales, one example of MSMEs in Surabaya City, especially in Rungkut Kidul Village, faces challenges in changing product branding and marketing strategies as part of the creative economy transformation. Various kinds of backgrounds that indicate the problems experienced by the residents of Rungkut Kidul Village are carried out community service activities involving students who take part in the KKN-T MBKM program aimed at planning an effective branding and marketing transformation strategy for these MSMEs so that their business can grow even more and its implementation takes place without any problems. The design of strategies used to solve problems and find solutions in this activity uses qualitative methods, through further observation, conducting question and answer activities covering parties involved with the problem to be researched, as well as perpetuating various physical or non-physical evidence from MSME activities. The results of this community service activity  show that the transformation of the creative economy in branding strategies and marketing digitalization for MSME product marketingis expected to  run well.